The Agency Model for Digital Goods. (14th September 2015) - Tan, Yinliang; Carrillo, Janice E.; Cheng, Hsing Kenny
ABSTRACT: While digital goods industries such as entertainment, software, and publishing are growing at a rapid pace, traditional supply chain contract models have failed to evolve with the new digital economy. To illustrate, the agency model utilized by the e‐book publishing industry has recently received much negative attention brought by the U.S. Department of Justice's lawsuit against Apple, Inc. The emerging agency model in the e‐book industry works as follows: the publisher sets the price of the digital goods and the retailers who serve as agents retain a percentage of the revenue associated with a consumer purchase. The regulators claim that the agency model is hurting this industry as well as the consumer's welfare because e‐book prices have increased after the introduction of the agency model. We investigate the strategic impact of the agency model by examining a digital goods supply chain with one supplier and two competing retailers. In comparison to the benchmark wholesale model, we find that the agency model can coordinate the competing retailers by dividing the coordinated profits into a prenegotiated revenue sharing proportion. Further, we also identify the Pareto improving region whereby both the supplier and the retailers prefer the agency model to the wholesale model. Our main qualitative insight regarding the agency model still holds even when we consider the presence of the printed books in the marketplace. Thus, contrary to current press presaging the negative impact of the agency model on the e‐books industry, we find the agency model to be superior to the traditional wholesale contracts for publishers, retailers and consumers in this digital goods industry.